Pomalidomide in heavily pretreated refractory multiple myeloma: a case report. (February 2017) - Palmas, Angelo; Piras, Giovanna; Uras, Antonella; Asproni, Rosanna; Murineddu, Marco; Monne, Maria; Stradoni, Roberta; Latte, Giancarlo
We present the case of a 70-year-old man diagnosed with multiple myeloma in 2008, who after four therapy lines initiated a fifth-line treatment with pomalidomide (4 mg orally, days 1–21 of a 28-day cycle) and low-dose dexamethasone (40 mg weekly orally). The patient was treated with pomalidomide for almost 2 years achieving a complete remission after 12 cycles. Complete remission was maintained for 9 months. This case illustrates the potential of pomalidomide plus low-dose dexamethasone to overcome multiple myeloma refractoriness inducing a quick and very prolonged remission.